2021
DOI: 10.1007/s11096-021-01310-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of intravenous admixture preparation errors: A prospective observational study in a university hospital

Abstract: Background Intravenous admixture preparation errors (IAPEs) may lead to patient harm. Insight into the prevalence as well as the determinants associated with these IAPEs is needed to elicit preventive measures. Aim The primary aim of this study was to assess the prevalence of IAPEs. Secondary aims were to identify the type, severity, and determinants of IAPEs. Method A prospective observational study was performed in a Dutch university hospital. IAPE data were collected by disguised observation. The primary ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
0
3
0
1
Order By: Relevance
“…One error type is incomplete mixing after a drug solution is added to the infusion fluid. Studies on the prevalence of this error type are scarce and have shown inconsistent results, with error rates varying from 0%-79% [ 1 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…One error type is incomplete mixing after a drug solution is added to the infusion fluid. Studies on the prevalence of this error type are scarce and have shown inconsistent results, with error rates varying from 0%-79% [ 1 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated many potential causes of medication preparation and administration errors, such as lack of knowledge, high workload, distractions, and inadequately written communication, but studies on IAPEs in particular are scarce 31–35 . With regard to risk factors of IAPEs in clinical wards, a study at our institution showed that especially multistep preparations (versus single-step preparations), interruptions during preparation, weekend preparations (versus weekday preparations), time window 2:00 pm to 6:00 pm (versus 7:00 am to 10:00 am ), and preparation in adult wards (versus pediatric wards) were associated with an increased probability of IAPEs 36 . To examine the causes of the IAPEs and noncompliance to hygiene procedures, robust qualitative studies are needed.…”
Section: Discussionmentioning
confidence: 86%
“… 31 35 With regard to risk factors of IAPEs in clinical wards, a study at our institution showed that especially multistep preparations (versus single-step preparations), interruptions during preparation, weekend preparations (versus weekday preparations), time window 2:00 pm to 6:00 pm (versus 7:00 am to 10:00 am ), and preparation in adult wards (versus pediatric wards) were associated with an increased probability of IAPEs. 36 To examine the causes of the IAPEs and noncompliance to hygiene procedures, robust qualitative studies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Jessurun и соавт. [18], выполненного методом скрытого наблюдения, ошибки при приготовлении смесей ЛП для инфузий были допущены медицинским персоналом в 367 из 614 случаев (59,8%) и состояли в неправильной технологии приготовления (n = 257) и в использовании неправильного объема раствора (n = 107).…”
Section: результаты и обсуждениеunclassified